Acute Colonic Pseudo-obstruction (Adynamic Ileus) after Cesarean Section: A Case Series - Retnowati, Sulistiari; Ivanna Beru Brahmana (HM Publisher, 2022)
Background. Maternal mortality is still high. The case that we will report below is an example of cases that can be happened in the hospital and can be ended with maternal mortality. Case presentation. A 30 years old disabled primigravida with ileus post- Caesarean Section day 5 was managed by relaparotomy and partial resection of caecum and ileum due to intestinal perforation, and die on the fifth days after relaparotomy due to sepsis. A-33 years old secundigravida with history of relaparotomy on 4 days after caesarean delivery in the first pregnancy due to ileus, was performed re-caesarean section due to unprogressed labor. Twelve hours after the operation the abdomen becomes distended and can be managed successfully by conservative early diagnosis management. A 29 years old primigravida has performed caesarean section with history of myomectomy 3 years ago. Twenty four hours after Caesarean Section, the abdomen becomes distended and early conservative management was done, but at 72 hours after the operation, there was intestinal perforation and performed colostomy. Conclusion. Acute colonic pseudoobstructive after caesarean section is a rare case, and delayed diagnosis and management increase the morbidity and mortality.